Pola Kepemimpinan Kiai dalam Modernisasi Manajemen Pesantren - Hasan, Zainul; Sugiono, Sugiono (AFKARINA: Jurnal Pendidikan Agama Islam, 2022)
This paper aims to analyze and examine how the figure of the kiai as the head of the Islamic boarding school manages the Islamic boarding school by modernizing management. Which leadership is required to have the ability to carry out innovations that are no longer relevant to the current situation in order to achieve the vision and mission of Islamic boarding schools. The research method used is qualitative research with a case study type. Data collection procedures through observation, interviews, and documentation. As well as data analysis used with data reduction, data display and data verification. The research focus in this study is: How is the kiai's leadership pattern in the modernization of pesantren management. The research method used is qualitative research with a case study type. Data collection procedures through observation, interviews, and documentation. As well as data analysis used with data reduction, data display and data verification. Based on the research that has been done, it is found that: The Kyai's Leadership Pattern in the Modernization of Islamic Boarding School Management consists of three main elements, namely: exemplary nature (Uswah Hasanah), attention to subordinates and service taining.